Prevalência de hemoglobina S em doadores de sangue do Hemocentro de Passo Fundo, Rio Grande do Sul, Brasil (Brazilian Journal of Health Research, 2018)
Prevalence of hemoglobin S in blood donors from the Blood Center of Passo Fundo, Rio Grande do Sul, Brazil